Representasi Tokoh Mistis Sundel Bolong pada Iklan Pocari Sweat Edisi Ramadan 2025 - Nadiva Aiszhabella; Alvian Alrasid Ajibulloh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the representation of the figure of the prolific sundel in the 2025 version of Pocari Sweat #IONTahanBocor advertisement using Roland Barthes' semiotic approach. The ad features a local mystical figure sundel bolong in an unusual humorous narrative to convey an educational message about the importance of staying hydrated during fasting. This study uses a descriptive qualitative method with a constructivist paradigm and analyzes visual impressions based on three layers of Barthes' meaning: denotation, connotation, and myth. The results of the analysis showed that the sundel bolong was shown as a figure who was dehydrated and then recovered after consuming Pocari Sweat, which is interpreted as a symbolic form of loss and recovery of body fluids. This representation shows a shift in meaning from a creepy figure to a funny and educational figure. Visual symbols such as the body leaking and the transformation into a cactus reinforce the educational message about hydration that is popularly packaged and lightweight. These findings suggest that advertising not only becomes a promotional medium, but also builds new myths through the construction of popular culture and visual communication.